Empoderamento econômico? Desenvolvimento feminino por meio do microcrédito no Brasil. - Botelho, Carla Mariana Café (2022)
This study aims to analyze how the economic empowerment of women helps in overcoming extreme poverty and allows the effective exercise of their fundamental rights, focusing the analysis on the public policy of financing through microcredit and on the realization of its role as an agent in the process of economic development. For this, initially, the main vulnerability factors of women in poverty are discussed. Then, the benefits that can be achieved through women's economic empowerment are explored, either for the individual condition of each woman or for the improvement of the development of a given society. The importance of creating public policies for women's economic empowerment is also understood and the applicability of financing through microcredit is analyzed as a measure to encourage improvement in the social condition of women in poverty and generate economic empowerment. In addition, the importance of public policies regarding the application of fundamental rights is discussed, emphasizing microcredit as a means of including people in the financial system. Finally, the main challenges of implementing microcredit in Brazil are presented, especially for the female audience, also understanding how state intervention takes place in this area, especially after the creation of the National Microcredit Policy (PNMPO). For this, qualitative research is used, of a descriptive nature, with a pure result. The research presented here also used a narrative bias with a focus on women telling their own story, which is why literatures are preferably feminine for the development of this work. As a result, microcredit, when combined with certain requirements, can serve as a skillful instrument to generate women's economic development, and consequently foster women's empowerment in various fields. Furthermore, for it to have better results in Brazil, it is necessary that the focus of applied programs be modified, focusing specifically on the poorest of the poor, as predicted by the original model fostered by the Bengali Muhammad Yunus. In addition, for the measure to be applied with a view to considering all the nuances that involve gender equality, the paradigm of feminist empowerment must be applied. Finally, it is understood that despite the criticism of the model currently used, the measures implemented after the creation of the National Microcredit Policy (PNMPO) tend to have positive long-term scenarios, with regard to the inclusion of the most vulnerable women in actively in the economy.